Pengaruh Kinerja UMKM Terhadap Pertumbuhan Ekonomi Kabupaten Sukabumi - Dasep Supriatna; Eki Candra; Iwan Adinugroho; Muhammad Amsal Nasution; Novi Yanti (Eastasouth Institute, 2023)
This study aims to analyze the effect of MSME performance on economic growth in Sukabumi Regency. The data used in this study were obtained from 100 respondents consisting of MSME owners or managers in the food sector. This study uses simple linear regression analysis to examine the relationship between MSME performance and economic growth. The results of the study show that the performance of MSMEs has a positive and significant influence on economic growth in Sukabumi Regency. The variation in economic growth in Sukabumi Regency can be explained by the performance of MSMEs. The local government and stakeholders must pay attention to and support the development of MSMEs, especially in the food sector, to encourage economic growth in Sukabumi Regency.